Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Alya Sasirangan Banjarmasin - Basmahu Syifa Arreishi; Farida Yulianti; Abdul Kadir; Noorlaily Maulida; Abdurrahim A (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to (1) To find out what marketing strategy was applied to Alya Sasirangan Banjarmasin in increasing sales of Sasirangan cloth products (2) To find out the strategy that should be carried out on Alya Sasirangan Banjarmasin in increasing sales of Sasirangan cloth. The method in this study uses a qualitative descriptive method. The informant in the study was the owner Alya Sasirangan Banjarmasin. Data collection techniques used in this study are observation techniques, interviews, and documentation studies.The results of the study show that Alya Sasirangan Banjarmasin has succeeded in implementing various and effective marketing strategies. They use digital platforms, such as WhatsApp, to promote products and increase interaction with customers. Apart from that, they also take advantage of traditional marketing through participation in local events and personal interactions. Word of mouth promotion strategy is also an important focus, by providing a satisfying experience to customers to expand the network and increase brand awareness. As for Alya Sasirangan Banjarmasin, they should be able to increase their visibility and brandbÂ image through various marketing strategies, by using advertising, direct selling, sales promotion, publicity and direct marketing, they can reach a wider audience, strengthen relationships with customers, and build a reputation as a source of reliable information. In this endeavor, it is important for them to provide clear messages, attractive designs, good service, and informative content. With the right strategy, Alya Sasirangan Banjarmasin can strengthen its position as a leading sasirangan brand and achieve success in this industry.